Diet with High Forage:Concentrate Ratio Improves Milk Nutritional Properties and Economic Sustainability of Buffalo Breeding - Lorenzo Infascelli; Nadia Musco; Piera Iommelli; Giuseppe Vassalotti; Francesco Capezzuto; Fabio Zicarelli; Valeria Maria Morittu; Anna Antonella Spina; Federico Infascelli; Raffaella Tudisco (Animals)
The present study aimed to evaluate the impact of two dietary regimens, characterized by different forage-to-concentrate ratios, on feed intake, milk yield and composition, as well as economic and environmental sustainability in lactating buffalo cows. Group H was fed a high-forage diet, while Group L was fed a diet with a lower forage-to-concentrate ratio. Despite a lower energy value (Unit for Feed Lactation: UFL 0.89 vs. 0.91), the diet of group H met the animals’ nutritional requirements, with similar dry matter intake (DMI) and body condition scores observed in both groups. While there was no significant difference in milk yield, protein, and lactose, group H exhibited significantly higher milk fat content and an enhanced fatty acid profile, characterized by increased oleic acid, conjugated linoleic acids (CLAs), and omega-3 polyunsaturated fatty acids. These fatty acids have been linked to potential health benefits in humans, including anti-inflammatory, cardioprotective, and anticarcinogenic effects. From an economic perspective, the H group’s diet was found to be more cost-effective, resulting in EUR 0.46 savings per head per day and a higher yield of mozzarella cheese. From an environmental perspective, the high-forage diet reduced reliance on imported concentrates and irrigation-dependent crops, aligning with sustainable development goals. In conclusion, increasing the forage content in buffalo diets has been demonstrated to support animal performance, improve milk quality, reduce environmental impact, and enhance economic returns for producers.